2022
DOI: 10.1002/eom2.12281
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances of non‐fullerene organic solar cells: From materials and morphology to devices and applications

Abstract: The innovation of non-fullerene acceptors (NFAs) enables the rapid progress of organic solar cells (OSCs) in power conversion efficiencies to over 19%, endowing OSCs with great potential toward real-world application. In this critical review, we outline the recent advances of NFA-based OSCs -from ITIC-to Y6-family, to exemplify the structure-performance correlations, and cover from material chemistry to nanomorphology controlling. In addition, we point out the possible degradation mechanisms behind the NFA-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 227 publications
0
29
0
Order By: Relevance
“…[3][4][5][6][7][8][9][10][11][12] To accelerate the improvement of the PCE of BDF-based OSCs, chemical and device engineering efforts should be carried out, as was conducted for BDT-based OSCs. [13][14][15][16][17][18][19][20][21] Suitable device engineering can significantly enhance the performance of a given material system. Compared with BDT-based polymer donors, whose material and device performances have been extensively studied, the progress of BDF-based systems has mainly been driven by material design, leaving great space for improvements from device engineering.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6][7][8][9][10][11][12] To accelerate the improvement of the PCE of BDF-based OSCs, chemical and device engineering efforts should be carried out, as was conducted for BDT-based OSCs. [13][14][15][16][17][18][19][20][21] Suitable device engineering can significantly enhance the performance of a given material system. Compared with BDT-based polymer donors, whose material and device performances have been extensively studied, the progress of BDF-based systems has mainly been driven by material design, leaving great space for improvements from device engineering.…”
Section: Introductionmentioning
confidence: 99%
“…[ 3–12 ] To accelerate the improvement of the PCE of BDF‐based OSCs, chemical and device engineering efforts should be carried out, as was conducted for BDT‐based OSCs. [ 13–21 ]…”
Section: Introductionmentioning
confidence: 99%
“…[6] Nevertheless, the device performance of PPDs lags behind that of OPDs based on SM-NFAs, because of the limited availability of polymeric NFAs and difficulties in controlling the morphologies of all-polymer blends. [7] Zhong et al reported a PPD incorporating an NT40:N2200 blend that displayed a value of D* of 2.61 × 10 13 Jones (−0.1 V) with a cut-off frequency at −3 dB (f −3 dB ) of 10 kHz. [7] Duan and co-workers employed the PBDB-T:PNDI-DTBT polymer pair to demonstrate a PPD that operated with a value of D* of 4.77 × 10 12 Jones (−0.1 V).…”
Section: Introductionmentioning
confidence: 99%
“…[7] Zhong et al reported a PPD incorporating an NT40:N2200 blend that displayed a value of D* of 2.61 × 10 13 Jones (−0.1 V) with a cut-off frequency at −3 dB (f −3 dB ) of 10 kHz. [7] Duan and co-workers employed the PBDB-T:PNDI-DTBT polymer pair to demonstrate a PPD that operated with a value of D* of 4.77 × 10 12 Jones (−0.1 V). [7] High sensitivity and a sub-microsecond response speed have been reported for a photomultiplication PPD developed for real-time testing of blood oxygen saturation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation